New electrolyte beverages prepared by the citrus canning processing water through chemical improvement - Sihuan Shen (Elsevier, 2021)
In the production of canned citrus, large amounts of processing water were discharged during the segment membrane removal process, causing severe pollution. In order to reduce pollution and recover the bioactive compounds in the processing water, the production of canned satsuma mandarin, sweet orange and grapefruit were studied, and improved acid (0.1% HCl, 0.4% citric acid) and alkali (0.1% KOH, 0.2% NaOH) were used to conduct the new chemical hydrolysis process to remove the segment membrane. The obtained acid and alkali processing water were firstly explored the potential to make novel beverages, which contain electrolytes (Na: 472–945 ppm; K: 208–279 ppm; Cl: 364–411 ppm; citrate: 1105–1653 ppm) and potential prebiotics such as pectin and flavonoids. The improved segment membrane removal process realized the conversion of wastewater into drinkable beverages at low costs. The bioactive compounds were fully recovered without wastewater discharging, which produced great environmental, economic and health value.